Análise estrutural de complexos contendo te(IV) nas formas aniônica e catiônica - Santos, Sailer Santos dos (2007)
In this work the synthesis and a detailed crystallochemical study of a series of complexes salts of Te(IV), with general formula [R3Te][PhTeX4] and [R3Te]2[TeX6], in which Te(IV) atoms appears in both cationic and anionic species, are presented. (R= phenyl or methyl, and X = Cl, Br or I). Diphenylditelluride (PhTe)2 was adopted as starting material for the preparation of phenyltellurium(IV) trihalides (PhTeX3) and also for the obtaintion of dimethylphenyltellurium(IV) derivatives ([PhMe2Te]X). The triphenyltelluronium derivatives were obtained from the direct reaction between benzene, TeCl4 and AlCl3, producing [Ph3Te]Cl, that is converted to the bromide and iodide analogues by ion exchange with the proper silver halide. The complexes [PhMe2Te][PhTeCl4] (1), [PhMe2Te][PhTeBr4] (2), [PhMe2Te][PhTeI4] (3), [Ph3Te][PhTeCl4] (4), [Ph3Te][PhTeBr4] (5) and [Ph3Te][PhTeI4] (6) were obtained from the mixture of methanolic solutions of the phenyltellurium(IV) trihalides with the proper triorganyltelluronium halide. The complexes [PhMe2Te]2[TeCl6] (7), [PhMe2Te]2[TeBr6] (8), and [Ph3Te]2[TeBr6] (9) were obtained from the solution of the tellurium(IV) tetrahalide in the proper halohidric acid followed by the addition of the respective triorganyltelluronium halide. Monocrystalls were obtained from acetonitrile. The complexes synthesized show secondary bonds between tellurium and halogen atoms, and these interactions are responsible for the different structural arrangement of each compound. The degree of extension of the Te...X secondary bonds is controlled by nature of the halogen bonded to tellurium and by the volume of the cation.